2022
DOI: 10.1007/s44178-022-00010-z
|View full text |Cite
|
Sign up to set email alerts
|

An appropriate treatment interval does not affect the prognosis of patients with breast Cancer

Abstract: Purpose Major public health emergencies may lead to delays or alterations in the treatment of patients with breast cancer at each stage of diagnosis and treatment. How much do these delays and treatment changes affect treatment outcomes in patients with breast cancer? Methods This review summarized relevant research in the past three decades and identified the effect of delayed treatment on the prognosis of patients with breast cancer in terms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Various factors influence the time to start of NAC including additional testing, for e.g., MRI, staging studies, and fertility preservation as indicated. Prior studies have demonstrated no impact on long term patient outcomes so long as NAC is initiated within 8 weeks of diagnosis [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors influence the time to start of NAC including additional testing, for e.g., MRI, staging studies, and fertility preservation as indicated. Prior studies have demonstrated no impact on long term patient outcomes so long as NAC is initiated within 8 weeks of diagnosis [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…BC patients are usually confronted with exigent anticancer treatments and excessive delays in initiating (neo) adjuvant chemotherapy have been shown to worsen the prognosis of breast cancer [19,20]. The process of FP generally takes approximately 2-4 weeks, including the time of consultation and performing COS in appropriate timing of menstruation.…”
Section: Discussionmentioning
confidence: 99%